Numerical and experimental investigations of buffet on a diamond airfoil designed for space launcher applications. Issue 9 (19th June 2019) - Dumon, Jéromine; Bury, Yannick; Gourdain, Nicolas; Michel, Laurent
Abstract : Purpose: The development of reusable space launchers requires a comprehensive knowledge of transonic flow effects on the launcher structure, such as buffet. Indeed, the mechanical integrity of the launcher can be compromised by shock wave/boundary layer interactions, that induce lateral forces responsible for plunging and pitching moments. Design/methodology/approach: This paper aims to report numerical and experimental investigations on the aerodynamic and aeroelastic behavior of a diamond airfoil, designed for microsatellite-dedicated launchers, with a particular interest for the fluid/structure interaction during buffeting. Experimental investigations based on Schlieren visualizations are conducted in a transonic wind tunnel and are then compared with numerical predictions based on unsteady Reynolds averaged Navier–Stokes and large eddy simulation (LES) approaches. The effect of buffeting on the structure is finally studied by solving the equation of the dynamics. Findings: Buffeting is both experimentally and numerically revealed. Experiments highlight 3D oscillations of the shock wave in the manner of a wind-flapping flag. LES computations identify a lambda-shaped shock wave foot width oscillations, which noticeably impact aerodynamic loads. At last, the experiments highlight the chaotic behavior of the shock wave as it shifts from an oscillatory periodic to an erratic 3D flapping state. Fluid structure computations show that the aerodynamic response of the airfoil tends to damp the structural vibrations and to mitigate the effect of buffeting. Originality/value: While buffeting has been extensively studied for classical supercritical profiles, this study focuses on diamond airfoils. Moreover, a fluid structure computation has been conducted to point out the effect of buffeting.